Interactive mathematics learning media based on problem-based learning to enhance students' numeracy skills - Kuswari Hernawati; Muhammad Irfan; Rofi Amiyani; Fadilla Zahira Jihan Mentari (Bulletin of Educational Management and Innovation, 2026)
Background: Numeracy skills are one of the essential competencies of the 21st century, but they remain low among Indonesian students, as demonstrated by national assessments and international studies. This situation demands learning innovations that integrate technology and problem-solving-cantered pedagogical approaches. Purpose: This study aims to develop and evaluate interactive mathematics learning media based on Problem-Based Learning (PBL) to improve students' numeracy skills. Method: This study used the Research and Development method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The subjects were eighth-grade junior high school students divided into an experimental class and a control class. The research instruments included an expert validation sheet, a student response questionnaire, and a numeracy test. Data analysis was conducted to test the validity, practicality, and effectiveness of the media, and an independent sample t-test was used to examine differences in learning outcomes. Findings: The results indicate that the developed media is highly valid, practical, and effective. Students using the media showed significantly higher improvements in numeracy skills compared to those in the control class. These findings demonstrate that integrating PBL within interactive media provides meaningful learning experiences and enhances students’ ability to apply mathematical concepts in real-life contexts.